Public Infrastructure in the Western Balkans : Opportunities and Challenges - Atoyan, Ruben (Departmental Papers; Departmental Paper, 2018)
An assessment of public infrastructure development in the Western Balkans. The paper quantifies the large gaps across various sectors/dimensions, evaluates current infrastructure plans, and discusses funding options available to countries in the region. The paper also identifies important bottlenecks for increased infrastructure investment. Finally, the paper quantifies potential growth benefits from addressing infrastructure gaps, concluding that boosting the quantity and quality of infrastructure is vital for raising economic growth and accelerating income convergence with the EU. The paper concludes with country-specific policy recommendations.